Pilgrims factors and the Nexus in Surat Al Qasas - Abbas yadollahi Farsani - Ali Halebed sharab - shuruq sandan sharshab ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The research deals with the study of the argumentative actors and links in Surat Al-Qasas, relying on the descriptive and analytical method. Through it, it was found that the connections formed a prominent effect on the orbital process, As well as its impact on interconnectedness and harmony. Therefore, the argumentative links have an advantage in linking arguments and results in explanation and removing ambiguity and ambiguity. The study proved that the relationships produced by the orbital connections vary according to the heterogeneity of the links, and this allows for a set of relationships. Among them, the relationship of sequence, causation, perception and explanation. The argumentative factors are based on the fact that they limit the significance of the speech to what the intended intention of the addressee. By directing an intended sign to the addressee, and this direction and restriction leads to the influence and persuasion that is obtained through the expressive means and the linguistic capabilities that the speaker has